Sergentomyia schwetzi is not a competent vector for Leishmania donovani and other Leishmania species pathogenic to humans - Sadlova, Jovana; Dvorak, Vit; Seblova, Veronika; Warburg, Alon; Votypka, Jan; Volf, Petr (Parasites & vectors, 2013)
BACKGROUND: Sand fly species of the genus Sergentomyia are proven vectors of reptilian Leishmania that are non-pathogenic to humans. However, a consideration of the role of Sergentomyia spp. in the circulation of mammalian leishmaniasis appears repeatedly in the literature and the possibility of Leishmania transmission to humans remains unclear. Here we studied the susceptibility of colonized Sergentomyia schwetzi to Leishmania donovani and two other Leishmania species pathogenic to humans: L. infantum and L. major. METHODS: Females of laboratory-reared S. schwetzi were infected by cultured Leishmania spp. by feeding through a chicken membrane, dissected at different time intervals post bloodmeal and examined by light microscopy for the abundance and location of infections. RESULTS: All three Leishmania species produced heavy late stage infections in Lutzomyia longipalpis or Phlebotomus duboscqi sand flies used as positive controls. In contrast, none of them completed their developmental cycle in Sergentomyia females; Leishmania promastigotes developed within the bloodmeal enclosed by the peritrophic matrix (PM) but were defecated together with the blood remnants, failing to establish a midgut infection. In S. schwetzi, the PM persisted significantly longer than in L. longipalpis and it was degraded almost simultaneously with defecation. Therefore, Leishmania transformation from procyclic to long nectomonad forms was delayed and parasites did not attach to the midgut epithelium. CONCLUSIONS: Sergentomyia schwetzi is refractory to human Leishmania species and the data indicate that the crucial aspect of the refractoriness is the relative timing of defecation versus PM degradation.
Keywords: virulence; Psychodidae; Leishmania donovani; ženské pohlaví; Insect Vectors; zvířata; Humans; Virulence; Leishmaniasis, Visceral; hmyz - vektory; leishmanióza viscerální; Female; lidé; Animals